Negative electrode composite current collector, composite pole piece, lithium battery and manufacturing method thereof

By using the structural design of polymer substrate layer, multiple discrete linear conductive structures, adhesive layer and composite layer in the negative electrode composite current collector of lithium battery, the problem of easy oxidation or corrosion of the end of lithium battery after cutting is solved. , achieving higher security and performance stability while saving copper resources.

CN117199389BActive Publication Date: 2025-01-24ADVANCED MATERIALS TECH (BEIJING) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311227768.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2023-09-21
Publication Date
2025-01-24
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

Lithium batteries are prone to oxidation or corrosion at the end of the cutting, resulting in a degradation of performance.

Method used

A negative polar composite fluid, including polymer substrate layer, multiple discrete line -type conductive structures, adhesive layers, and composite layers. Combining force and setting the coverage layer outside the conductivity to prevent corrosion.

Benefits of technology

Effectively prevent the exposed and corroded of the conductive layer at the end of the lithium battery during the cutting process, improve the safety and performance stability of the battery, while saving copper resources and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117199389B_ABST
    Figure CN117199389B_ABST
Patent Text Reader

Abstract

The present disclosure provides a negative electrode composite current collector, a composite pole piece, a lithium battery and a manufacturing method thereof, wherein the negative electrode composite current collector comprises: a polymer substrate layer; a first conductive layer, arranged on one side of the polymer substrate layer, the first conductive layer comprising a plurality of discrete first linear conductive structures; a first adhesive layer, arranged between the first conductive layer and the polymer substrate layer; a first composite layer, arranged on one side of the first conductive layer away from the polymer substrate layer and between the plurality of discrete first linear conductive structures; a second conductive layer, arranged on one side of the polymer substrate layer away from the first conductive layer, the second conductive layer comprising a plurality of discrete second linear conductive structures; a second adhesive layer, arranged between the second conductive layer and the polymer substrate layer; and a second composite layer, arranged on one side of the second conductive layer away from the polymer substrate layer and between the plurality of discrete second linear conductive structures.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This disclosure claims priority to Chinese Patent Application No. 202310804530.0 filed in China on June 30, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present disclosure relates to the technical field of lithium batteries, and in particular to a negative electrode composite current collector, a composite pole piece, a lithium battery and a manufacturing method thereof. Background Art

[0004] Lithium-ion batteries, or lithium batteries for short, are widely used in people's daily lives as a highly efficient energy storage device. Traditional lithium-ion battery cells contain pairs of positive and negative electrodes, which are stacked in multiple layers or wound together to create battery cells of different capacities. In traditional lithium-ion batteries, aluminum foil is used as the positive current collector metal material, and copper foil is used as the negative current collector metal material. In the process of preparing lithium batteries, cutting the current collector easily exposes the cut end, leading to oxidation or corrosion of the copper or aluminum end. Summary of the invention

[0005] The purpose of the present disclosure is to provide a composite negative electrode current collector, a composite pole piece, a lithium battery and a manufacturing method thereof, which can at least solve the current technical problem of oxidation or corrosion of the end portion of the lithium battery after cutting.

[0006] The present disclosure provides a negative electrode composite current collector for a lithium battery, wherein the negative electrode composite current collector comprises:

[0007] a polymer substrate layer;

[0008] A first conductive layer, disposed on one side of the polymer substrate layer, the first conductive layer comprising a plurality of discrete first linear conductive structures;

[0009] a first bonding layer disposed between the first conductive layer and the polymer substrate layer and configured to bond the first conductive layer and the polymer substrate layer;

[0010] A first composite layer is disposed on a side of the first conductive layer away from the polymer substrate layer and between a plurality of discrete first linear conductive structures;

[0011] A second conductive layer, disposed on a side of the polymer substrate layer away from the first conductive layer, the second conductive layer comprising a plurality of discrete second linear conductive structures;

[0012] a second bonding layer disposed between the second conductive layer and the polymer substrate layer and configured to bond the second conductive layer and the polymer substrate layer;

[0013] A second composite layer is disposed on a side of the second conductive layer away from the polymer substrate layer and between a plurality of discrete second linear conductive structures;

[0014] The plurality of discrete first linear conductive structures and the plurality of discrete second linear conductive structures are symmetrically arranged relative to the polymer substrate layer.

[0015] In some embodiments,

[0016] The orthographic projection of the first adhesive layer on the polymer substrate layer overlaps with the orthographic projection of the first conductive layer on the polymer substrate layer; and

[0017] The orthographic projection of the second adhesive layer on the polymer substrate layer overlaps with the orthographic projection of the second conductive layer on the polymer substrate layer.

[0018] In some embodiments,

[0019] The orthographic projection of the first adhesive layer on the polymer substrate layer overlaps with the polymer substrate layer; and

[0020] The second adhesive layer overlaps the polymer substrate layer in an orthographic projection of the polymer substrate layer.

[0021] In some embodiments,

[0022] The orthographic projection of the first composite layer on the polymer substrate layer covers the orthographic projection of the first conductive layer on the polymer substrate layer; and

[0023] The orthographic projection of the second composite layer on the polymer substrate layer covers the orthographic projection of the second conductive layer on the polymer substrate layer.

[0024] In some embodiments,

[0025] The first composite layer comprises:

[0026] A first barrier layer is disposed on a side of the first conductive layer away from the polymer substrate layer,

[0027] A first intermediate layer is disposed on a side of the first barrier layer close to the first conductive layer and configured to prevent diffusion between the first barrier layer and the first conductive layer; and

[0028] The second composite layer comprises:

[0029] A second barrier layer is disposed on a side of the second conductive layer away from the polymer substrate layer,

[0030] The second intermediate layer is disposed on a side of the second barrier layer close to the second conductive layer and is configured to prevent diffusion between the second barrier layer and the second conductive layer.

[0031] In some embodiments,

[0032] The first bonding layer, the first barrier layer and the first intermediate layer overlap with the orthographic projection of the polymer substrate layer; and

[0033] The second adhesive layer, the second barrier layer and the second intermediate layer overlap with each other in orthographic projection on the polymer substrate layer.

[0034] In some embodiments, the polymer substrate layer is selected from at least one of acrylonitrile-butadiene-styrene copolymer, polyterephthalate, polybutylene terephthalate, poly(p-phenylene terephthalamide), polyimide, polyamide, polyethylene, polystyrene, polyvinylidene fluoride, polyvinyl chloride, polytetrafluoroethylene, polypropylene, polypropylene, polycarbonate, polyoxymethylene, epoxy resin and phenolic resin.

[0035] In some embodiments,

[0036] The tensile strength of the material of the polymer substrate layer is ≥150 MPa; or

[0037] The thermal shrinkage of the material of the polymer substrate layer after being treated at 150° C. for 30 minutes is ≤3%; or

[0038] The thickness of the polymer substrate layer is 1-15 μm.

[0039] In some embodiments,

[0040] The material of the first conductive layer and / or the second conductive layer is selected from at least one of the following:

[0041] A single metal with a purity of ≥98wt% is selected from the following: aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten; or;

[0042] Selected from alloys, wherein the metal in the alloy is selected from at least one of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum, tungsten, manganese, magnesium and zinc, and / or the non-metal in the alloy is selected from silicon and / or carbon.

[0043] In some embodiments,

[0044] The thickness of the first conductive layer and / or the second conductive layer is 0.1-2 μm respectively; or,

[0045] The bonding force between the first conductive layer and / or the second conductive layer and the polymer substrate layer is ≥ 0.5 N / 15 mm;

[0046] The resistivity of the first conductive layer and / or the second conductive layer is ≤8 μΩ·cm.

[0047] In some embodiments,

[0048] The material of the first conductive layer and / or the second conductive layer includes Al, and the material of the first barrier layer and / or the second barrier layer includes Cu.

[0049] In some embodiments,

[0050] The material of the first barrier layer and / or the second barrier layer is selected from at least one of the following:

[0051] A single metal with a purity of ≥98wt% is selected from the following: aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten; or;

[0052] Selected from alloys, wherein the metal in the alloy is selected from at least one of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum and tungsten.

[0053] In some embodiments,

[0054] The thickness of the first barrier layer and the second barrier layer are 1-1500 nm respectively; or,

[0055] The bonding force between the first barrier layer and the first conductive layer and / or the bonding force between the second barrier layer and the second conductive layer is ≥ 0.5 N / 15 mm.

[0056] In some embodiments,

[0057] The material of the first intermediate layer and / or the second intermediate layer is selected from at least one of the following: a single metal, an alloy, an oxide semiconductor or a conductive compound.

[0058] In some embodiments,

[0059] The material of the first intermediate layer and / or the second intermediate layer is selected from at least one of the following:

[0060] The single metal is selected from one of Cu, Cr, Ta, Zn, Cd, In, Tl, Mn, Co, Mo, Fe, Sn, Ge, Bi, Sb, Re, Ti, V, Ni, Nb and Tc;

[0061] The metal in the alloy is selected from at least one of Cu, Cr, Ta, Zn, Cd, In, Tl, Mn, Co, Mo, Fe, Sn, Ge, Bi, Sb, Re, Ti, V, Ni, Nb and Tc;

[0062] The oxide semiconductor is selected from at least one of Cu2O, ZnO, SnO2, Fe2O3, TiO2, ZrO2, Co2O3, WO3, In2O3, Al2O3 and Fe3O4;

[0063] The conductive compound is selected from at least one of TiB2, TiC, TiN, ZrB2, ZrC, ZrN, VB2, VC, VN, NbB2, NbC, NbN, TaB2, TaC, CrB2, Cr3C2, CrN, Mo2C, Mo2B5, W2B5, WC and LaB6.

[0064] In some embodiments, the thickness of the first intermediate layer and / or the second intermediate layer is 1-1000 nm.

[0065] In some embodiments, the first barrier layer and the second barrier layer are made of the same material, the first conductive layer and the second conductive layer are made of the same material; the first intermediate layer and the second intermediate layer are made of the same material; the first barrier layer, the first conductive layer and the first intermediate layer are made of different materials.

[0066] In some embodiments, the material of the first bonding layer and / or the second bonding layer is selected from at least one of the following: a single metal or an alloy or a metal compound;

[0067] Wherein, the single metal is selected from at least one of Cu, Cr, Ta, Zn, Cd, In, Tl, Mn, Co, Mo, Fe, Sn, Ge, Bi, Sb, Re, Ti, V, Ni, Nb and Tc;

[0068] The alloy is at least one of a nickel-based alloy and an aluminum-based alloy;

[0069] The metal compound is at least one of AlOx, TiB2, TiC, TiN, ZrB2, ZrC, ZrN, VB2, VC, VN, NbB2, NbC, NbN, TaB2, TaC, CrB2, Cr3C2, CrN, Mo2C, Mo2B5, W2B5, WC and LaB6.

[0070] In some embodiments, the first bonding layer and / or the second bonding layer is prepared by at least one of the following methods: magnetron sputtering, ion plating, vacuum evaporation or in-situ reaction.

[0071] The present disclosure also provides a composite pole piece, which includes the negative electrode composite current collector as described above.

[0072] The present disclosure also provides a lithium battery, comprising the composite pole piece as described above.

[0073] The present disclosure also provides a method for manufacturing a negative electrode composite current collector, the manufacturing method comprising:

[0074] providing a polymer substrate layer;

[0075] Disposing a first adhesive layer on one side of the polymer substrate layer;

[0076] A first conductive layer is disposed on a side of the first bonding layer away from the polymer substrate layer, wherein the first conductive layer includes a plurality of discrete first linear conductive structures;

[0077] Disposing a first composite layer on a side of the first conductive layer away from the polymer substrate layer, and disposing the first composite layer between a plurality of discrete first linear conductive structures;

[0078] Disposing a second bonding layer on a side of the polymer substrate layer away from the first bonding layer;

[0079] A second conductive layer is disposed on a side of the second adhesive layer away from the polymer substrate layer, wherein the second conductive layer includes a plurality of discrete second linear conductive structures;

[0080] Disposing a second composite layer on a side of the second conductive layer away from the polymer substrate layer, and disposing a second composite layer between a plurality of discrete second linear conductive structures;

[0081] The plurality of discrete first linear conductive structures and the plurality of discrete second linear conductive structures are symmetrically arranged relative to the polymer substrate layer.

[0082] In some embodiments,

[0083] Disposing a first composite layer on a side of the first conductive layer away from the polymer substrate layer, and disposing the first composite layer between a plurality of discrete first linear conductive structures comprises:

[0084] Disposing a first intermediate layer on a side of the first barrier layer close to the first conductive layer;

[0085] a first barrier layer is disposed on a side of the first intermediate layer away from the polymer substrate layer, wherein the first intermediate layer is configured to prevent diffusion between the first barrier layer and the first conductive layer, and

[0086] Disposing a second composite layer on a side of the second conductive layer away from the polymer substrate layer, and disposing a second composite layer between a plurality of discrete second linear conductive structures comprises:

[0087] Disposing a second intermediate layer on a side of the second barrier layer close to the second conductive layer;

[0088] A second barrier layer is disposed on a side of the second intermediate layer away from the polymer substrate layer, wherein the second intermediate layer is configured to prevent diffusion between the second barrier layer and the second conductive layer.

[0089] In some embodiments, the method of disposing a first conductive layer on the side of the first bonding layer away from the polymer substrate layer and / or disposing a second conductive layer on the side of the second bonding layer away from the polymer substrate layer comprises: one or more of evaporation, deposition and sputtering.

[0090] The present disclosure also provides a method for manufacturing a composite electrode sheet, including the method for manufacturing a negative electrode composite current collector as described in any one of the above items.

[0091] The present disclosure also provides a method for manufacturing a lithium battery, including the method for manufacturing the composite pole piece as described above.

[0092] Compared with the related art, the present invention has the following technical effects:

[0093] 1. The negative electrode composite current collector provided in the present disclosure can replace traditional copper as the negative electrode current collector, saving copper resources and costs;

[0094] 2. The barrier layer in the present disclosure is a continuous and dense thin film structure, which can prevent the alloying of the negative electrode Li-Al material and improve the conductivity of the composite current collector;

[0095] 3. Use PVD method to design the bonding layer structure between the polymer layer and the conductive layer to enhance the bonding force between the polymer layer and the conductive layer;

[0096] 4. A covering layer is provided outside the discrete linear conductive structure in the negative electrode composite current collector disclosed in the present invention, which can prevent Li-Al end corrosion during cutting and application;

[0097] 5. The negative electrode composite current collector disclosed in the present invention can be made very thin, which can improve the effective energy volume ratio of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0098] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0099] Figure 1 A schematic diagram of the cross-sectional structure of a negative electrode composite current collector cut along line N provided in some embodiments of the present disclosure;

[0100] Figure 2 A schematic diagram of the cross-sectional structure of another side of the negative electrode composite current collector provided in some embodiments of the present disclosure;

[0101] Figure 3 A schematic diagram of the cross-sectional structure of a negative electrode composite current collector provided in some other embodiments of the present disclosure;

[0102] Figure 4 A flow chart of a method for manufacturing a composite current collector provided in some embodiments of the present disclosure;

[0103] Figure 5 A flow chart of a method for manufacturing a composite current collector provided for other embodiments of the present disclosure; and

[0104] Figure 6 A flow chart of a method for manufacturing a composite current collector provided in some other embodiments of the present disclosure. DETAILED DESCRIPTION

[0105] In order to make the purpose, technical solutions and advantages of the present disclosure clearer, the present disclosure will be further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0106] The terms used in the embodiments of the present disclosure are only for the purpose of describing specific embodiments, and are not intended to limit the present disclosure. The singular forms "a", "said" and "the" used in the embodiments of the present disclosure and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0107] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0108] It should be understood that although the terms first, second, third, etc. may be used to describe in the present disclosure, these should not be limited to these terms. These terms are only used to distinguish. For example, without departing from the scope of the present disclosure, the first may also be referred to as the second, and similarly, the second may also be referred to as the first.

[0109] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such product or device. In the absence of more restrictions, the elements defined by the sentence "comprises a" do not exclude the presence of other identical elements in the product or device including the elements.

[0110] In the related art, lithium batteries usually include positive and negative electrodes, and the positive and negative electrodes are stacked in multiple layers or wound in positive and negative electrodes to achieve battery cells of different capacities. The positive electrode usually includes a positive current collector and a positive active material coated on both sides of the positive current collector. The positive current collector usually uses aluminum foil, and the thickness of the aluminum foil is generally 10 to 15 microns. The negative electrode usually includes a negative current collector and a negative active material coated on both sides of the negative current collector. The negative current collector usually uses copper foil, and the thickness of the copper foil is generally 4.5 to 9 microns. Lithium-ion batteries generally use aluminum as the positive current collector metal material and copper as the negative current collector metal material. This is because the oxidation potential of aluminum is high, and the size of the octahedral voids in the aluminum lattice is similar to that of lithium, making it very easy for aluminum to react with lithium to form alloys such as LiAl, Li3Al2, and Li4Al3, which not only consumes a large amount of Li+, but also destroys the structure and morphology of aluminum itself. Therefore, aluminum can be used as a current collector for the positive electrode of lithium-ion batteries, but not as a current collector for the negative electrode of lithium-ion batteries. Cu has only a small amount of lithium insertion capacity during the battery charge and discharge process, and maintains the stability of the structure and electrochemical properties, so it can be used as a current collector for the negative electrode of ion batteries.

[0111] The positive electrode active material is coated on both sides of the aluminum foil, and then baked, rolled, slit, and die-cut to make the positive electrode sheet. The negative electrode active material is coated on both sides of the copper foil, and then baked, rolled, slit, and die-cut to make the negative electrode sheet. Then the negative electrode sheet / diaphragm / positive electrode sheet are stacked or wound in sequence to make the lithium battery cell. Since the aluminum foil and copper foil are relatively thick, the positive electrode collector and the negative electrode collector occupy a considerable volume, resulting in a low effective energy volume ratio of the lithium battery, which is not conducive to the miniaturization of the lithium battery.

[0112] The embodiment of the present disclosure provides a negative electrode composite current collector for a lithium battery, the negative electrode composite current collector comprising: a polymer substrate layer; a first conductive layer, arranged on one side of the polymer substrate layer, the first conductive layer comprising a plurality of discrete first linear conductive structures; a first bonding layer, arranged between the first conductive layer and the polymer substrate layer, and configured to bond the first conductive layer and the polymer substrate layer; a first composite layer, arranged on one side of the first conductive layer away from the polymer substrate layer and between the plurality of discrete first linear conductive structures; a second conductive layer, arranged on one side of the polymer substrate layer away from the first conductive layer, the second conductive layer comprising a plurality of discrete second linear conductive structures; a second bonding layer, arranged between the second conductive layer and the polymer substrate layer, and configured to bond the second conductive layer and the polymer substrate layer; a second composite layer, arranged on one side of the second conductive layer away from the polymer substrate layer and between the plurality of discrete second linear conductive structures; wherein the plurality of discrete first linear conductive structures and the plurality of discrete second linear conductive structures are symmetrically arranged relative to the polymer substrate layer.

[0113] The optional embodiments of the present disclosure are described in detail below with reference to the accompanying drawings.

[0114] Figure 1 A schematic diagram of the cross-sectional structure of a negative electrode composite current collector cut along line N provided in some embodiments of the present disclosure; Figure 2A schematic diagram of the cross-sectional structure of another side of a negative electrode composite current collector provided in some embodiments of the present disclosure; specifically, an embodiment of the present disclosure provides a negative electrode composite current collector 100 for a lithium battery, wherein the negative electrode composite current collector 100 comprises: a polymer substrate layer 1; a first conductive layer 2, wherein the first conductive layer 2 is disposed on one side of the polymer substrate layer 1, and the first conductive layer 2 comprises a plurality of discrete first linear conductive structures; a first bonding layer 8, wherein the first bonding layer 8 is disposed between the first conductive layer 2 and the polymer substrate layer 1, and is configured to bond the first conductive layer 2 and the polymer substrate layer 1; a first composite layer 10, wherein the first composite layer 10 is disposed on one side of the first conductive layer 2 away from the polymer substrate layer 1 and a plurality of discrete first linear conductive structures; The first linear conductive structure is disposed between the first linear conductive structures; a second conductive layer 3, the second conductive layer 3 is disposed on the side of the polymer substrate layer 1 away from the first conductive layer 2, and the second conductive layer 3 includes a plurality of discrete second linear conductive structures; a second bonding layer 9, the second bonding layer 9 is disposed between the second conductive layer 3 and the polymer substrate layer 1, and is configured to bond the second conductive layer 3 and the polymer substrate layer 1; a second composite layer 10, the second composite layer 10 is disposed on the side of the second conductive layer 3 away from the polymer substrate layer 1 and between a plurality of discrete second linear conductive structures; wherein the plurality of discrete first linear conductive structures and the plurality of discrete second linear conductive structures are symmetrically disposed relative to the polymer substrate layer.

[0115] Among them, Figure 2 As shown, the first conductive layer 2 includes a plurality of discrete first linear conductive structures, the second conductive layer 3 includes a plurality of discrete second linear conductive structures, the first linear conductive structures and the second linear conductive structures are respectively wrapped by the first composite layer 10 and the second composite layer 20, when a small area of ​​the negative electrode composite current collector 100 is cut out from a large area of ​​the negative electrode composite current collector 100, for example, when the negative electrode composite current collector 100 is used for the assembly of the lithium battery, it can be cut out along the first composite layer 100 and the second composite layer 20 is wrapped by the first composite layer 10 and the second composite layer 20. Figure 2 The M-line cutting will not cause the ends of the first conductive layer 2 and the second conductive layer 3 to be exposed, thus preventing the first conductive layer 2 and the second conductive layer 3 from being oxidized or corroded due to exposure to the air. The first linear conductive structure and the second linear conductive structure can be straight-line or curved structures, as long as they are discretely and roughly arranged in parallel along the surface of the polymer substrate layer 1, the problem of exposed ends due to cutting can be solved. The multiple discrete first linear conductive structures and the multiple discrete second linear conductive structures are symmetrically arranged relative to the polymer substrate layer, ensuring that when cutting, it is possible to cut from the groove on one side (no conductive layer) to the corresponding groove on the other side (no conductive layer), and avoid cutting the conductive layer to expose it.

[0116] In some embodiments, Figure 2As shown, the orthographic projection of the first composite layer 10 on the polymer substrate layer 1 covers the orthographic projection of the first conductive layer 2 on the polymer substrate layer 1; and the orthographic projection of the second composite layer 20 on the polymer substrate layer 1 covers the orthographic projection of the second conductive layer 3 on the polymer substrate layer 1. The projections of the first linear conductive structure and the second linear conductive structure on the polymer substrate layer 1 are roughly overlapped, so that it can be ensured that as long as cutting is carried out between the linear conductive structures, the ends of the first conductive layer 2 and the second conductive layer 3 will not be exposed.

[0117] In some embodiments, Figure 2 As shown, the orthographic projection of the first adhesive layer 8 on the polymer substrate layer 1 overlaps with the orthographic projection of the first conductive layer 2 on the polymer substrate layer 1; and the orthographic projection of the second adhesive layer 9 on the polymer substrate layer 1 overlaps with the orthographic projection of the second conductive layer 3 on the polymer substrate layer 1, so as to ensure that the first conductive layer 2 is completely bonded to the polymer substrate layer 1, and the second conductive layer 3 is completely bonded to the polymer substrate layer 1. In the formation process, for example, a mask can be set to deposit an adhesive material in the mask gap by magnetron sputtering, ion plating, vacuum evaporation or in-situ reaction, and then a conductive layer is deposited, so as to form a structure in which the conductive layer and the adhesive layer are stacked, so that the conductive layer can be stably combined with the polymer substrate layer through the adhesive layer.

[0118] In some other embodiments, Figure 3 As shown, the first adhesive layer 8 overlaps with the polymer substrate layer 1 in its orthographic projection; and the second adhesive layer 9 overlaps with the polymer substrate layer 1 in its orthographic projection, and then a first conductive layer 2 is formed on the first adhesive layer 8, and a second conductive layer 3 is formed on the second adhesive layer 9, so as to ensure that the first conductive layer 2 is completely bonded to the polymer substrate layer 1, and the second conductive layer 3 is completely bonded to the polymer substrate layer 1. In the formation process, for example, the adhesive material can be deposited on both sides of the polymer substrate layer 1 by magnetron sputtering, ion plating, vacuum evaporation or in-situ reaction, and then a mask is set to deposit a conductive layer in the gap of the mask by magnetron sputtering, ion plating, vacuum evaporation or in-situ reaction, so as to form a structure in which the conductive layer and the adhesive layer are stacked, so that the conductive layer can be stably combined with the polymer substrate layer through the adhesive layer.

[0119] In some embodiments, the polymer substrate layer 1 is selected from at least one of acrylonitrile-butadiene-styrene copolymer, polyterephthalate, polybutylene terephthalate, poly(p-phenylene terephthalamide), polyimide, polyamide, polyethylene, polystyrene, polyvinylidene fluoride, polyvinyl chloride, polytetrafluoroethylene, polypropylene, polypropylene, polycarbonate, polyoxymethylene, epoxy resin and phenolic resin. Compared with the traditional copper foil layer, the polymer substrate layer is lighter and can be set thinner, which is conducive to reducing the volume of the lithium battery and improving the performance of the lithium battery.

[0120] In some embodiments, the tensile strength of the material of the polymer substrate layer 1 is ≥150MPa, preferably 150-400MPa; the polymer substrate layer 1 is used to support the entire negative electrode composite current collector. During the deposition process of the negative electrode composite current collector, the coating roller pressing process of the electrode sheet requires the support of a high tensile strength polymer substrate layer to avoid roll breakage and deformation. Therefore, when the tensile strength is <150Mpa, it cannot meet the supporting function during the coating roller pressing process, and roll breakage and deformation are prone to occur. The thermal shrinkage rate of the material of the polymer substrate layer 1 after being treated at 150°C for 30 minutes is ≤3%. If the thermal shrinkage rate of the polymer substrate layer 1 is too large, it will also cause the negative electrode composite current collector to break and deform. Therefore, this embodiment has been verified by experiments that the thermal shrinkage rate of the material of the polymer substrate layer 1 after being treated at 150°C for 30 minutes should be less than or equal to 3% to meet the negative electrode composite current collector production process; the thickness of the polymer substrate layer 1 is 1-15μm, preferably 1-10μm. If the polymer substrate layer 1 is too thick, the volume of the negative electrode composite current collector and the internal resistance of the lithium battery will be increased. Therefore, the polymer substrate layer 1 with a thickness in the above range is selected in the present disclosure. The polymer substrate layer 1 has the characteristics of light weight, good ductility, high tensile strength, and low thermal shrinkage, which can effectively reduce the volume and weight of the lithium battery. Moreover, due to the presence of the polymer substrate layer 1, even if the conductive layer is broken down, it will not form a short circuit of the battery, thereby improving the safety of the battery.

[0121] In some embodiments, the material of the first conductive layer 2 and / or the second conductive layer 3 is selected from at least one of the following: selected from a single metal with a purity of ≥98wt%: aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten; preferably one of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum and tungsten with a purity of 99-100wt%; or; selected from an alloy, wherein the metal in the alloy is selected from at least one of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum, tungsten, manganese, magnesium and zinc, and / or the non-metal in the alloy is selected from silicon and / or carbon. Preferably, the alloy is selected from at least one of aluminum-copper alloy, aluminum-manganese alloy, aluminum-silicon alloy, aluminum-magnesium alloy, aluminum-magnesium-silicon alloy and aluminum-zinc alloy. The higher the purity of the conductive layer material, the better the conductivity, which is more conducive to enhancing the conductive efficiency.

[0122] In some embodiments, the first conductive layer 2 and / or the second conductive layer 3 are most preferably made of aluminum, which has the characteristics of good conductivity, light weight, low price, good flexibility, etc. Therefore, in this embodiment, aluminum is preferably used as the conductive material when preparing the first conductive layer 2 and / or the second conductive layer 3. Aluminum is selected as the material of the first conductive layer 2 and / or the second conductive layer 3, and an aluminum layer is deposited on the polymer substrate layer 1 by PVD, which enhances the conductivity, and the aluminum layer is wrapped between the polymer substrate layer and the composite layer, which overcomes the defect that aluminum cannot be used as a negative electrode in traditional lithium batteries, further reduces the thickness of the negative electrode without weakening the conductive performance of the negative electrode.

[0123] In some embodiments, the thickness of the first conductive layer 2 and / or the second conductive layer 3 is 0.1-2 μm, respectively; preferably 0.2-1.5 μm; vacuum equipment can achieve vacuum deposition at the micron level. The thicker the metal conductive layer, the lower the resistance. However, the thickening of the metal layer increases the difficulty of the process feasibility. In the experiment disclosed in this disclosure, a film of 800 nanometers to 2000 nm can be formed at one time. Through the optimization of process parameters, the resistivity of the metal film in the thickness range of 800 to 1500 nm is relatively stable. For the directional movement of free electrons in the conductive layer, as long as it is a continuous film (thickness ≥ 30 nm), a stable conductive effect can be formed. However, if the conductive layer is too thin, due to the excessive size effect of the metal film, the resistivity will be very high, affecting the internal resistance of the battery cell. Therefore, after experiments, the present disclosure selects a conductive layer with a thickness of more than 200 nm.

[0124] In some embodiments, the bonding force between the first conductive layer 2 and / or the second conductive layer 3 and the polymer substrate layer 1 is ≥0.5N / 15mm, so as to avoid the first conductive layer 2 and / or the second conductive layer 3 being peeled off from the polymer substrate layer 1 during curling or application, thereby affecting the conductivity.

[0125] In some embodiments, the resistivity of the first conductive layer 2 and / or the second conductive layer 3 is ≤8 μΩ·cm.

[0126] Due to the different inherent properties of the materials, the interface bonding between the polymer substrate layer and the metal conductive layer is not strong, because there is only van der Waals force between the two, and no chemical bond exists. Therefore, the desired composite current collector structure is a composite structure with high conductivity and high bonding strength. The greater the bonding force, the better, ≥0.5N / 15mm, with no upper limit. The resistivity of the bulk metal material is ≤ the resistivity of the composite current collector ≤8uΩ·cm.

[0127] In some embodiments, the first composite layer 10 includes: a first barrier layer 4, which is disposed on the side of the first conductive layer 2 away from the polymer substrate layer 1, a first intermediate layer 6, which is disposed on the side of the first barrier layer 4 close to the first conductive layer 2, and the first intermediate layer 6 is configured to prevent diffusion between the first barrier layer 4 and the first conductive layer 2; and the second composite layer 20 includes: a second barrier layer 5, which is disposed on the side of the second conductive layer 3 away from the polymer substrate layer 1, a second intermediate layer 7, which is disposed on the side of the second barrier layer 5 close to the second conductive layer 3, and the second intermediate layer 7 is configured to prevent diffusion between the second barrier layer 5 and the second conductive layer 3. The first composite layer 10 and the second composite layer 20 completely wrap the first conductive layer 2 and the second conductive layer 3, making aluminum a feasible solution as a negative electrode, and due to the discrete structural design and the wrapped composite layer, the problem of exposing the end of the aluminum layer due to cutting when making a lithium battery is overcome.

[0128] In some embodiments, the material of the first barrier layer 4 and / or the second barrier layer 5 is selected from at least one of the following: selected from a single metal with a purity ≥98wt%: aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten; preferably one of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum and tungsten with a purity of 99-100wt%; or; selected from an alloy, wherein the metal in the alloy is selected from at least one of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum and tungsten; further preferably, the alloy is selected from at least one of copper-aluminum alloy, copper-nickel alloy, copper-zinc alloy and copper-tin alloy.

[0129] In some embodiments, the thickness of the first barrier layer 4 and the second barrier layer 5 are respectively 1-1500 nm, preferably 30-1000 nm; compared with the traditional copper foil negative electrode, the first barrier layer 4 and the second barrier layer 5 can be deposited with a thinner copper layer by PVD, saving copper materials and reducing the overall thickness of the negative electrode sheet.

[0130] In some embodiments, the bonding force between the first barrier layer 4 and the first conductive layer 2 and / or the bonding force between the second barrier layer 5 and the second conductive layer 3 is ≥0.5N / 15mm. The strong bonding force prevents the first barrier layer 4 from peeling off from the first conductive layer 2 or the second barrier layer 5 from peeling off from the second conductive layer 3 during curling or application, thereby affecting the conductivity.

[0131] The function of the barrier layer is to prevent the exposure of the conductive layer Al. This operation can be achieved as long as the barrier layer is a continuous and dense film (for example, thickness ≥ 30nm). Another function of the barrier layer is conductivity. However, if the barrier layer is too thin (tens of nanometers), it will diffuse with the conductive layer in a short period of time (a few days or weeks), exposing Al and losing the original function of the barrier layer. If the barrier layer is too thick, it will increase the process cost, material utilization efficiency, etc. Therefore, the barrier layer can be set between 1 and 1500nm, preferably 30-1000nm.

[0132] The conductive layer and the barrier layer will have a weak interface bonding phenomenon, because there is only van der Waals force between the two, and there is no chemical bond. In addition, an aluminum oxide film will naturally form on the aluminum surface of the conductive layer, resulting in a low bonding strength between Cu and Al. If CuAl is delaminated due to low bonding strength during the use of the battery, it will lose its conductive function. Therefore, it is hoped that the bonding strength between the two is ≥0.5N / 15mm.

[0133] Since aluminum is used as the conductive layer and the aluminum composite current collector is used as the negative electrode, it will undergo an alloying reaction with metallic lithium, resulting in failure of the conductive performance. Therefore, a barrier layer (Cu) is provided on the aluminum layer to form an aluminum-copper composite layer. While not reducing the conductivity, it can block the alloying reaction between Li-Al and improve the stability of the lithium battery.

[0134] In some embodiments, when Al as a conductive layer and Cu as a barrier layer are both at the negative electrode, Al-Cu interdiffusion and galvanic corrosion may occur under the action of the electrolyte. Designing an intermediate layer between Al and Cu can prevent or slow down the interdiffusion and corrosion between Al and Cu, and at the same time can also play a conductive role and enhance the bonding force between aluminum and copper. Specifically, the material of the first intermediate layer 6 and / or the second intermediate layer 7 is selected from at least one of the following: a single metal, an alloy, an oxide semiconductor or a conductive compound.

[0135] In some embodiments, the material of the first intermediate layer 6 and / or the second intermediate layer 7 is selected from at least one of the following: the single metal is selected from one of Cu, Cr, Ta, Zn, Cd, In, Tl, Mn, Co, Mo, Fe, Sn, Ge, Bi, Sb, Re, Ti, V, Ni, Nb and Tc; the metal in the alloy is selected from at least one of Cu, Cr, Ta, Zn, Cd, In, Tl, Mn, Co, Mo, Fe, Sn, Ge, Bi, Sb, Re, Ti, V, Ni, Nb and Tc A method of manufacturing a semiconductor material comprising: the oxide semiconductor being selected from at least one of Cu2O, ZnO, SnO2, Fe2O3, TiO2, ZrO2, Co2O3, WO3, In2O3, Al2O3 and Fe3O4; and the conductive compound being selected from at least one of TiB2, TiC, TiN, ZrB2, ZrC, ZrN, VB2, VC, VN, NbB2, NbC, NbN, TaB2, TaC, CrB2, Cr3C2, CrN, Mo2C, Mo2B5, W2B5, WC and LaB6. Preferably, the first intermediate layer 6 and / or the second intermediate layer 7 are respectively selected from at least one of nickel, nickel-based alloy, copper-based alloy and titanium nitride, preferably titanium nitride.

[0136] In some embodiments, the thickness of the first intermediate layer 6 and / or the second intermediate layer 7 is 1-1000nm, preferably 5-500nm. The intermediate layer plays the role of conducting electricity, enhancing the bonding strength between CuAl, and preventing the mutual diffusion of the two. Generally, it will be thinner. As long as it plays the above role, it is as thin as possible to save raw materials and costs. Generally, the film will be 1-1000nm, preferably 5nm-100nm or 5nm-500nm.

[0137] In some embodiments, the first barrier layer 4 and the second barrier layer 5 are made of the same material, the first conductive layer 2 and the second conductive layer 3 are made of the same material; the first intermediate layer 6 and the second intermediate layer 7 are made of the same material; the first barrier layer 4, the first conductive layer 2 and the first intermediate layer 6 are made of different materials. In some embodiments, the material of the first conductive layer 2 and / or the second conductive layer 3 includes Al, and the material of the first barrier layer 4 and / or the second barrier layer 5 includes Cu.

[0138] Example:

[0139] Example 1: A 1 um thick Al layer was vacuum deposited on the upper and lower surfaces of a 6 um thick PET substrate, and a 300 nm thick Cu layer was vacuum evaporated on the upper and lower surfaces of the Al layer. A battery was prepared to characterize the initial efficiency and cycle performance of the battery, and to compare the corrosion of the battery pole after disassembly.

[0140] Example 2: AlOx with a thickness of 10 nm was in-situ reacted on the upper and lower surfaces of a 6 um thick PET substrate, and an Al layer with a thickness of 1 um was continuously formed, and a Cu layer with a thickness of 300 nm was vacuum evaporated on the upper and lower surfaces of the Al layer. A battery was prepared, and the first efficiency and cycle performance of the battery were characterized, and the corrosion of the battery pole piece after disassembly was compared.

[0141] Example 3: AlOx with a thickness of 10 nm was generated by in-situ reaction on the upper and lower surfaces of a 6-um thick PET substrate, and an Al layer with a thickness of 1 um was formed. A Ni layer with a thickness of 10 nm was magnetron sputtered on the upper and lower surfaces of the Al layer, and a Cu layer with a thickness of 300 nm was vacuum evaporated on the upper and lower surfaces of the Ni layer. A battery was prepared, and the initial efficiency and cycle performance of the battery were characterized, and the corrosion of the battery pole piece after disassembly was compared.

[0142] Example 4: A NiCr layer with a thickness of 10 nm was magnetron sputtered on the upper and lower surfaces of a PET substrate with a thickness of 6 μm, an Al layer with a thickness of 1 μm was vacuum evaporated on the upper and lower surfaces of the NiCr layer, a Ni layer with a thickness of 10 nm was magnetron sputtered on the upper and lower surfaces of the Al layer, and a Cu layer with a thickness of 300 nm was vacuum evaporated on the upper and lower surfaces of the Ni layer. A battery was prepared, and the first efficiency and cycle performance of the battery were characterized, and the corrosion of the battery pole piece after disassembly was compared.

[0143] Example 5: A Ti layer with a thickness of 10 nm was magnetron sputtered on the upper and lower surfaces of a PET substrate with a thickness of 6 μm, an Al layer with a thickness of 1 μm was vacuum evaporated on the upper and lower surfaces of the Ti layer, a Ni layer with a thickness of 10 nm was magnetron sputtered on the upper and lower surfaces of the Al layer, and a Cu layer with a thickness of 300 nm was vacuum evaporated on the upper and lower surfaces of the Ni layer. A battery was prepared, and the first efficiency and cycle performance of the battery were characterized, and the corrosion of the battery pole piece after disassembly was compared.

[0144] Example 6: A NiAl layer with a thickness of 10 nm was magnetron sputtered on the upper and lower surfaces of a PET substrate with a thickness of 6 um, an Al layer with a thickness of 1 um was vacuum evaporated on the upper and lower surfaces of the NiAl layer, a Ni layer with a thickness of 10 nm was magnetron sputtered on the upper and lower surfaces of the Al layer, and a Cu layer with a thickness of 300 nm was vacuum evaporated on the upper and lower surfaces of the Ni layer. A battery was prepared, and the initial efficiency and cycle performance of the battery were characterized, and the corrosion of the battery pole piece after disassembly was compared.

[0145] In the comparative example, 1um metal Al was directly evaporated on the upper and lower surfaces of a 6um thick PET substrate, and the composite current collector after film formation was used as the negative electrode current collector to prepare a battery. The initial efficiency and cycle performance of the battery were characterized, and the corrosion of the battery pole pieces after disassembly was compared.

[0146] Table 1 Comparison of composite current collector core performance

[0147] serial number Square resistance mΩ / sq Binding force N / 15mm First effect% 1C cycle - number of turns Is the battery powdered? Example 1 26.92 4.36 91.5 1163 no Example 2 26.88 8.45 91.24 1165 no Example 3 26.29 8.26 91.45 1189 no Example 4 26.82 7.38 91.71 1152 no Example 5 26.55 7.29 91.27 1141 no Example 6 26.32 7.74 91.36 1153 no Comparative Example 32.13 4.36 91.23 / yes

[0148] It can be seen from the performance comparison results of the composite current collectors in Table 1 that the square resistance values ​​of Examples 1 to 6 of the present application are relatively low, all lower than 27 mΩ / sq, while the square resistance value of the comparative example is higher than 32 mΩ / sq, indicating that the composite current collectors formed in the embodiments of the present application have good conductivity.

[0149] In Examples 2 to 6 of the present application, an adhesive layer is added between the Al layer and the substrate, and the bonding force is increased from 4.36 N / 15 mm to 7-8 N / 15 mm, which greatly increases the bonding force of the composite current collector.

[0150] The first coulombic efficiency of Examples 1 to 6 of the present application is close to that of the comparative example, indicating that the composite current collector battery cells formed in the embodiments of the present application have good discharge performance.

[0151] Comparison of Examples 1 to 6 of the present application with the comparative example shows that the first effects of Examples 1 to 6 and the comparative example are substantially the same, while the internal resistance is significantly reduced. In addition, the number of cycles of Examples 1 to 6 is relatively high, indicating that the composite current collector is well applied as a negative electrode current collector.

[0152] It can be seen from the battery results in Table 1 that the embodiments 1 to 6 of the present invention can be used as negative electrode current collectors (among which the binding force of embodiments 2 to 6 is better), and the battery performance is good. After disassembling the battery, the barrier layer Cu does not pulverize, while the comparative battery is directly pulverized after disassembly, indicating that Al cannot be directly applied to the negative electrode. The present disclosure also provides a composite pole piece, which includes the negative electrode composite current collector 100 described in the above embodiment.

[0153] The present disclosure also provides a lithium battery, comprising the composite pole piece as described in the above embodiment.

[0154] The present disclosure also provides a method for manufacturing a negative electrode composite current collector 100, such as Figure 4 As shown, the manufacturing method comprises the following steps:

[0155] Step S102: providing a polymer substrate layer;

[0156] Step S104: providing a first adhesive layer on one side of the polymer substrate layer;

[0157] Step S106: disposing a first conductive layer on a side of the first adhesive layer away from the polymer substrate layer, wherein the first conductive layer includes a plurality of discrete first linear conductive structures;

[0158] Step S108: disposing a first composite layer on a side of the first conductive layer away from the polymer substrate layer and between a plurality of discrete first linear conductive structures;

[0159] Step S110: disposing a second bonding layer on a side of the polymer substrate layer away from the first bonding layer;

[0160] Step S112: disposing a second conductive layer on a side of the second adhesive layer away from the polymer substrate layer, wherein the second conductive layer includes a plurality of discrete second linear conductive structures;

[0161] Step S114: disposing a second composite layer on a side of the second conductive layer away from the polymer substrate layer and between a plurality of discrete second linear conductive structures;

[0162] The plurality of discrete first linear conductive structures and the plurality of discrete second linear conductive structures are symmetrically arranged relative to the polymer substrate layer.

[0163] In some embodiments, Figure 5 As shown, step S108 includes the following sub-steps:

[0164] Step S108-1: disposing a first intermediate layer on a side of the first barrier layer close to the first conductive layer;

[0165] Step S108 - 2 : disposing a first barrier layer on a side of the first intermediate layer away from the polymer substrate layer, wherein the first intermediate layer is configured to prevent diffusion between the first barrier layer and the first conductive layer.

[0166] In some embodiments, Figure 6 As shown, step S114 includes the following sub-steps:

[0167] Step S114-1: disposing a second intermediate layer on a side of the second barrier layer close to the second conductive layer;

[0168] Step S114 - 2 : disposing a second barrier layer on a side of the second intermediate layer away from the polymer substrate layer, wherein the second intermediate layer is configured to prevent diffusion between the second barrier layer and the second conductive layer.

[0169] In some embodiments, the method of disposing a first conductive layer on the side of the first bonding layer away from the polymer substrate layer and / or disposing a second conductive layer on the side of the second bonding layer away from the polymer substrate layer comprises: one or more of evaporation, deposition and sputtering.

[0170] The present disclosure also provides a method for manufacturing a composite electrode sheet, including the method for manufacturing the negative electrode composite current collector 100 as described in any one of the above items.

[0171] The present disclosure also provides a method for manufacturing a lithium battery, including the method for manufacturing the composite pole piece as described above.

[0172] The thickness of the negative electrode composite electrode sheet formed by the negative electrode composite current collector disclosed in the present invention can be made very thin compared with the negative electrode sheet of a conventional lithium battery, and can be used to improve the effective energy volume ratio of the lithium battery; in addition, the negative electrode current collector provided in the present invention can replace the traditional copper as the negative electrode current collector, saving copper resources and costs and improving safety; the barrier layer in the present invention is a continuous and dense thin film structure, which can prevent the alloying of the negative electrode Li-Al material and can improve the conductivity of the composite current collector; the bonding layer structure is designed between the polymer layer and the conductive layer by the PVD method to enhance the bonding force between the polymer layer and the conductive layer; the negative electrode composite current collector disclosed in the present invention can prevent Li-Al end corrosion during the cutting application process.

[0173] Finally, it should be noted that: the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0174] The above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them. Although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present disclosure.

Claims

1. A negative electrode composite current collector for a lithium battery, characterized in that: The negative electrode composite current collector comprises: a polymer substrate layer; A first conductive layer, disposed on one side of the polymer substrate layer, wherein the first conductive layer is a plurality of discrete first linear conductive structures; a first bonding layer disposed between the first conductive layer and the polymer substrate layer and configured to bond the first conductive layer and the polymer substrate layer; A first composite layer is disposed on a side of the first conductive layer away from the polymer substrate layer and between a plurality of discrete first linear conductive structures; A second conductive layer is disposed on a side of the polymer substrate layer away from the first conductive layer, wherein the second conductive layer is a plurality of discrete second linear conductive structures; a second bonding layer disposed between the second conductive layer and the polymer substrate layer and configured to bond the second conductive layer and the polymer substrate layer; A second composite layer is disposed on a side of the second conductive layer away from the polymer substrate layer and between a plurality of discrete second linear conductive structures; Wherein, the plurality of discrete first linear conductive structures and the plurality of discrete second linear conductive structures are symmetrically arranged relative to the polymer substrate layer; The first composite layer comprises: A first barrier layer is disposed on a side of the first conductive layer away from the polymer substrate layer, A first intermediate layer is disposed on a side of the first barrier layer close to the first conductive layer and configured to prevent diffusion between the first barrier layer and the first conductive layer; and The second composite layer comprises: A second barrier layer is disposed on a side of the second conductive layer away from the polymer substrate layer, a second intermediate layer, disposed on a side of the second barrier layer close to the second conductive layer, and configured to prevent diffusion between the second barrier layer and the second conductive layer; The material of the first bonding layer and / or the second bonding layer is selected from at least one of the following: a single metal or an alloy or a metal compound; Wherein, the single metal is selected from at least one of Cu, Cr, Ta, Zn, Cd, In, Tl, Mn, Co, Mo, Fe, Sn, Ge, Bi, Sb, Re, Ti, V, Ni, Nb and Tc; The alloy is at least one of a nickel-based alloy and an aluminum-based alloy; The metal compound is at least one of TiB2, TiC, TiN, ZrB2, ZrC, ZrN, VB2, VC, VN, NbB2, NbC, NbN, TaB2, TaC, CrB2, Cr3C2, CrN, Mo2C, Mo2B5, W2B5, WC and LaB6.

2. The negative electrode composite current collector according to claim 1, characterized in that: The orthographic projection of the first adhesive layer on the polymer substrate layer overlaps with the orthographic projection of the first conductive layer on the polymer substrate layer; as well as, The orthographic projection of the second adhesive layer on the polymer substrate layer overlaps with the orthographic projection of the second conductive layer on the polymer substrate layer.

3. The negative electrode composite current collector according to claim 1, characterized in that: The orthographic projection of the first adhesive layer on the polymer substrate layer overlaps with the polymer substrate layer; and The second adhesive layer overlaps the polymer substrate layer in an orthographic projection of the polymer substrate layer.

4. The negative electrode composite current collector according to claim 1, characterized in that: The orthographic projection of the first composite layer on the polymer substrate layer covers the orthographic projection of the first conductive layer on the polymer substrate layer; and The orthographic projection of the second composite layer on the polymer substrate layer covers the orthographic projection of the second conductive layer on the polymer substrate layer.

5. The negative electrode composite current collector according to claim 1, characterized in that: The first bonding layer, the first barrier layer and the first intermediate layer overlap with the orthographic projection of the polymer substrate layer; and The second adhesive layer, the second barrier layer and the second intermediate layer overlap with each other in orthographic projection on the polymer substrate layer.

6. The negative electrode composite current collector according to claim 1, characterized in that: The polymer substrate layer is selected from at least one of acrylonitrile-butadiene-styrene copolymer, polyterephthalate, polybutylene terephthalate, poly(p-phenylene terephthalamide), polyimide, polyamide, polyethylene, polystyrene, polyvinylidene fluoride, polyvinyl chloride, polytetrafluoroethylene, polypropylene, polypropylene, polycarbonate, polyoxymethylene, epoxy resin and phenolic resin.

7. The negative electrode composite current collector according to claim 1, characterized in that: The tensile strength of the material of the polymer substrate layer is ≥150 MPa; or The thermal shrinkage rate of the material of the polymer substrate layer after being treated at 150° C. for 30 minutes is ≤3%; or The thickness of the polymer substrate layer is 1-15 μm.

8. The negative electrode composite current collector according to claim 1, characterized in that: The material of the first conductive layer and / or the second conductive layer is selected from at least one of the following: A single metal with a purity of ≥98wt% is selected from the following: aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten; or; Selected from alloys, wherein the metal in the alloy is selected from at least one of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum, tungsten, manganese, magnesium and zinc, and / or the non-metal in the alloy is selected from silicon and / or carbon.

9. The negative electrode composite current collector according to claim 1, characterized in that: The thickness of the first conductive layer and / or the second conductive layer is 0.1-2 μm respectively; or, The bonding force between the first conductive layer and / or the second conductive layer and the polymer substrate layer is ≥ 0.5 N / 15 mm; The resistivity of the first conductive layer and / or the second conductive layer is ≤8 μΩ•cm.

10. The negative electrode composite current collector according to claim 1, characterized in that: The material of the first conductive layer and / or the second conductive layer includes Al, and the material of the first barrier layer and / or the second barrier layer includes Cu.

11. The negative electrode composite current collector according to claim 1, characterized in that: The material of the first barrier layer and / or the second barrier layer is selected from at least one of the following: A single metal with a purity of ≥98wt% is selected from the following: aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten; or; Selected from alloys, wherein the metal in the alloy is selected from at least one of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum and tungsten.

12. The negative electrode composite current collector according to claim 1, characterized in that: The thickness of the first barrier layer and the second barrier layer are 1-1500 nm respectively; or, The bonding force between the first barrier layer and the first conductive layer and / or the bonding force between the second barrier layer and the second conductive layer is ≥ 0.5 N / 15 mm.

13. The negative electrode composite current collector according to claim 1, characterized in that: The material of the first intermediate layer and / or the second intermediate layer is selected from at least one of the following: a single metal, an alloy, an oxide semiconductor or a conductive compound.

14. The negative electrode composite current collector according to claim 13, characterized in that: The material of the first intermediate layer and / or the second intermediate layer is selected from at least one of the following: The single metal is selected from one of Cu, Cr, Ta, Zn, Cd, In, Tl, Mn, Co, Mo, Fe, Sn, Ge, Bi, Sb, Re, Ti, V, Ni, Nb and Tc; The metal in the alloy is selected from at least one of Cu, Cr, Ta, Zn, Cd, In, Tl, Mn, Co, Mo, Fe, Sn, Ge, Bi, Sb, Re, Ti, V, Ni, Nb and Tc; The oxide semiconductor is selected from at least one of Cu2O, ZnO, SnO2, Fe2O3, TiO2, ZrO2, Co2O3, WO3, In2O3, Al2O3 and Fe3O4; The conductive compound is selected from at least one of TiB2, TiC, TiN, ZrB2, ZrC, ZrN, VB2, VC, VN, NbB2, NbC, NbN, TaB2, TaC, CrB2, Cr3C2, CrN, Mo2C, Mo2B5, W2B5, WC and LaB6.

15. The negative electrode composite current collector according to claim 1, characterized in that: The thickness of the first intermediate layer and / or the second intermediate layer is 1-1000 nm.

16. The negative electrode composite current collector according to claim 1, characterized in that: The first barrier layer and the second barrier layer are made of the same material, the first conductive layer and the second conductive layer are made of the same material; the first intermediate layer and the second intermediate layer are made of the same material; the first barrier layer, the first conductive layer and the first intermediate layer are made of different materials.

17. The negative electrode composite current collector according to claim 1, characterized in that: The first bonding layer and / or the second bonding layer is prepared by at least one of the following methods: magnetron sputtering, ion plating, vacuum evaporation or in-situ reaction.

18. A composite pole piece, characterized in that: The composite electrode sheet comprises the negative electrode composite current collector according to any one of claims 1 to 17.

19. A lithium battery, characterized in that: Including the composite pole piece as described in claim 18.

20. A method for manufacturing a negative electrode composite current collector, characterized in that: The manufacturing method comprises: providing a polymer substrate layer; Disposing a first adhesive layer on one side of the polymer substrate layer; A first conductive layer is disposed on a side of the first bonding layer away from the polymer substrate layer, wherein the first conductive layer is a plurality of discrete first linear conductive structures; Disposing a first composite layer on a side of the first conductive layer away from the polymer substrate layer, and disposing the first composite layer between a plurality of discrete first linear conductive structures; Disposing a second bonding layer on a side of the polymer substrate layer away from the first bonding layer; A second conductive layer is disposed on a side of the second adhesive layer away from the polymer substrate layer, wherein the second conductive layer is a plurality of discrete second linear conductive structures; Disposing a second composite layer on a side of the second conductive layer away from the polymer substrate layer, and disposing a second composite layer between a plurality of discrete second linear conductive structures; Wherein, the plurality of discrete first linear conductive structures and the plurality of discrete second linear conductive structures are symmetrically arranged relative to the polymer substrate layer; The first composite layer comprises: A first barrier layer is disposed on a side of the first conductive layer away from the polymer substrate layer, A first intermediate layer is disposed on a side of the first barrier layer close to the first conductive layer and configured to prevent diffusion between the first barrier layer and the first conductive layer; and The second composite layer comprises: A second barrier layer is disposed on a side of the second conductive layer away from the polymer substrate layer, a second intermediate layer, disposed on a side of the second barrier layer close to the second conductive layer, and configured to prevent diffusion between the second barrier layer and the second conductive layer; The material of the first bonding layer and / or the second bonding layer is selected from at least one of the following: a single metal or an alloy or a metal compound; Wherein, the single metal is selected from at least one of Cu, Cr, Ta, Zn, Cd, In, Tl, Mn, Co, Mo, Fe, Sn, Ge, Bi, Sb, Re, Ti, V, Ni, Nb and Tc; The alloy is at least one of a nickel-based alloy and an aluminum-based alloy; The metal compound is at least one of TiB2, TiC, TiN, ZrB2, ZrC, ZrN, VB2, VC, VN, NbB2, NbC, NbN, TaB2, TaC, CrB2, Cr3C2, CrN, Mo2C, Mo2B5, W2B5, WC and LaB6.

21. The manufacturing method according to claim 20, characterized in that: Disposing a first composite layer on a side of the first conductive layer away from the polymer substrate layer, and disposing the first composite layer between a plurality of discrete first linear conductive structures comprises: Disposing a first intermediate layer on a side of the first barrier layer close to the first conductive layer; a first barrier layer is disposed on a side of the first intermediate layer away from the polymer substrate layer, wherein the first intermediate layer is configured to prevent diffusion between the first barrier layer and the first conductive layer, and Disposing a second composite layer on a side of the second conductive layer away from the polymer substrate layer, and disposing a second composite layer between a plurality of discrete second linear conductive structures comprises: Disposing a second intermediate layer on a side of the second barrier layer close to the second conductive layer; A second barrier layer is disposed on a side of the second intermediate layer away from the polymer substrate layer, wherein the second intermediate layer is configured to prevent diffusion between the second barrier layer and the second conductive layer.

22. The manufacturing method according to claim 20, characterized in that: The method of disposing the first conductive layer on the side of the first adhesive layer away from the polymer substrate layer and / or disposing the second conductive layer on the side of the second adhesive layer away from the polymer substrate layer comprises: one or more of evaporation, deposition and sputtering.

23. A method for manufacturing a composite pole piece, characterized in that: A method for manufacturing a negative electrode composite current collector comprising the steps of any one of claims 20 to 22.

24. A method for manufacturing a lithium battery, characterized in that: Including the method for manufacturing the composite pole piece as described in claim 23.

Citation Information

Patent Citations

  • Current collector, pole piece thereof and electrochemical device

    CN109873164A

  • Composite current collector for negative electrode of lithium ion battery and preparation method of composite current collector

    CN114864951A

  • Positive current collector of lithium ion battery and positive pole piece including same

    CN204088469U